Implementasi Algoritma C5.0 Untuk Memprediksi Kondisi Kelahiran Bayi - Siti Sahara Nasution; Natalia Silalahi; Abdul Karim (Bulletin of Computer Science Research, 2021)
The condition of birth is the condition of the birth of a baby is one of the main problems in the health sector that is currently happening in Indonesia. In health, there are several indicators of birth conditions, namely normal and caesarean. Determining the degree of condition of the baby's birth is a reflection of the current status of the baby's birth. Children as the nation's successor are closely related to the growth and development of babies today. However, the implementation to improve infant growth and development is still not optimal. This study produces a decision tree of the cases raised showing that there are several attributes that influence the determination of birth conditions. A list of gain values for each attribute will be displayed. The position of the attribute that has the highest gain value displayed indicates the determination of which attribute is the determination of eligibility